Pendampingan Pengurusan Pensertifikatan Tanah wakaf yang dikelola Oleh Pimpinan Daerah Muhammadiyah Kabupaten Malang - Cahyani, Tinuk Dwi; Luthfi, Muhammad (Community Empowerment, 2021)
This community dedication program is a collaborative service program with PDM Kab. Malang in solving the problem of waqf certification on managed assets. The purpose of this service is to assist and provide education in terms of waqf certification problems. The method used in this service is by analyzing assets and mentoring partners. This community dedication is carried out in the DAU sub-district by taking 3 waqf objects. From the three waqf objects, the 2 objects are found in the data that 2 waqf objects have not made a waqf pledge and waqf certification on the first and second objects, while 1 object has made a waqf pledge but the waqf certification has not been registered, namely the third object. With regard to 2 objects that have not made a wakaf pledge and waqf certification, the community dedication Team coordinates with a Nadzir to analyze the administrative requirements of the waqf pledge process and complete the waqf pledge document process. In the process of analyzing and completing the data, there are different requirements because the first waqf object is a waqf object that already has a land title in the form of SHM, while in the second waqf object is a waqf object that does not have a land title base in the form of a Village Letter C Book Quote. The registration process for the certification of 3 waqf objects is carried out through 2 processes, namely the first, the registration process for the waqf certificate on land that already has a document of entitlement, namely in the first object, and the second, the process for registering a waqf certificate on land that does not have a document of entitlement, namely on the second and third objects.